Comparative genetic diagnostic evaluation of pediatric neuromuscular diseases in a consanguineous population - Abdullah Al-Hedaithy; Fouad Alghamdi; Momen Almomen; Fawzia Amer; Shaikhah Al Dossari; Deeba Noreen Baig; Shahid Bashir (Scientific Reports)
Abstract Neuromuscular diseases (NMD) are a group of neurological diseases that manifest with various clinical symptoms affecting different components of the peripheral nervous system, which play a role in voluntary body movements control. The primary objective of this study is to explore the diagnostic efficacy of a combined genetic and biochemical testing approach for patients with neuromuscular diseases with diverse presentations in a population with high rate of consanguinity. Genetic testing was performed using selected Next Generation Sequencing (NGS) gene panels and whole exome sequencing on the peripheral blood sample from the patients. The study results revealed that the majority of patients in our cohort had a history of consanguinity (83%). Genetic testing through gene panels and Whole Exome Sequencing yielded similar result. Out of the patients tested, 66% underwent gene panels testing, 56% had Whole Exome Sequencing, 32% received array Comparative Genomic Hybridization (CGH) assays, and 40% underwent metabolic testing. Overall, 58 patients (61%) received definitive results after following all tests. Among the remaining 36 patients, 19 exhibited variants of unknown significance (VOUS) (21%).